Study of correlation between age of menarche and body mass index in adolescent - Agrawal, Megha; Agrawal, Anshul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Younger age at menarche is associated with higher body mass index (BMI) for adolescents. Obesity has a strong association with infertility and menstrual irregularities. Higher BMI at menarche is associated with an earlier occurrence of menarche. The timing of menarche was associated with the BMI, waist circumference, thickness of skin fold, but more strongly so with the BMI. Methods: This cross-sectional study was conducted at Durgapur (West Bengal), where total 600 adolescent girls aged 12-17 years from DAV Model School, Durgapur and GMPS High School, Durgapur were selected. Results: In studied girls, maximum girls 267 (44.5%) attained menarche at age of 13 years. 129 girls (21.5%) had menarche at age of 12 years. 87 girls (14.5%) had menarche at age of 11 years. 77 girls (12.8%) had menarche at age of 14 years. 39 girls (6.5%) had menarche at age of 15 years. Only 1 girl (0.2%) had menarche at age of 10 years. 119 girls with BMI of <18.5 kg/m2 had mean age of menarche 12.92±1.03 years. 357 girls with BMI of 18.5-24.99 kg/m2 had mean age of menarche 12.74±1.07 years. 124 girls with BMI of >25 kg/m2 had mean age of menarche 12.60±1.07 years. Conclusions: Mean age of menarche in adolescent girls was 12.75±1.06 year. Mean BMI was found 21.6±3.64 kg/m2. High BMI girls had earlier menarche, comparatively to normal BMI girls and underweight girls.